Trails of hope and terror - De La Torre, Vincent; De La Torre, Miguel A.; De La Torre, Deborah ([Mexico] : V1 Educational Media, Inc., 2016)
Trails of Hope and Terror is a 53-minute documentary that ends with the stories of two teenage girls, Sandra and Josseline. One encounters the border (La Frontera) by accident, and the other on purpose. But their journeys, along with the others we hear about in the film, began hundreds of years ago, as complicated political and economic strategies set up a vast system from which there is little hope of escape. Manifest Destiny, the Mexican-American War, Gun-Boat Diplomacy, Banana Republics, NAFTA, Operation Gatekeeper. . . all of these political events led up to a system of "prevention through deterrence." In other words, if people were forced to cross a desert in where they were likely to die, then they might think twice about the risks. The fact is, no one was deterred. In Trails of Hope and Terror, we will hear stories about the people whose families needed them. At the time, they felt it was the right thing to do. So they crossed anyway. --
In Spanish and English; with English subtitles for Spanish dialogs.
Semi finalist Social World Film Festival, 2017
Winner Cine Miami Fest, 2017
Winner (In) Justice for All Film Festival, 2017
Winner Mediterranean Film Festival Cannes, 2016
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 4, 2022)
Keywords: Mexican-American Border Region -- Emigration and immigration; Mexico -- Emigration and immigration -- History; United States -- Emigration and immigration -- History; Documentary films; Historical films; Streaming video